Analysis of Sodium, Potassium and Calcium using a Portable Liquid Electrode Plasma Optical Emission Spectrometer - Hidayanto, Eko; Yamamoto, Takashi; Kawai, Jun (BERKALA FISIKA, 2011)
Elements of sodium (Na), potassium (K) and calcium (Ca) in beverage samples and river water were analyzed with portable liquid electrode plasma - optical emission spectrometer (LEP-OES). The degree of reproducibility for emission intensities and individual variety of a disposal sample chip were investigated, and measuring conditions for quantitative analysis and the precision was discussed. The sensitivity for Na was higher than those for K and Ca by one or two orders of magnitude. Several ppm of Na and K, and several hundred of Ca in aqueous samples could be quantitatively analyzed with 2-30% of deviation without internal standard. The applied voltage was predominant factor for accurate quantitative analysis, and 800 V was found to be the best voltage estimation for quantitative analysis of alkaline metals contents.